2012
DOI: 10.4103/1119-3077.100625
|View full text |Cite
|
Sign up to set email alerts
|

Oral health practices among pregnant women in North Eastern Nigeria

Abstract: Oral healthcare among the respondents was encouraging but involvement of the dental surgeon in preventive oral care in pregnancy is rather dismal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…showed that 55.8% of pregnant mothers exercised oral and dental care twice a day. (19) Similarly, Halah et al found that most of the mothers (73.7%) reported good habits of oral and dental health care, such as tooth brushing twice a day. (20) Martinez et al reported that several pregnant mothers (84%) brushed their teeth two or three times a day.…”
Section: Discussionmentioning
confidence: 93%
“…showed that 55.8% of pregnant mothers exercised oral and dental care twice a day. (19) Similarly, Halah et al found that most of the mothers (73.7%) reported good habits of oral and dental health care, such as tooth brushing twice a day. (20) Martinez et al reported that several pregnant mothers (84%) brushed their teeth two or three times a day.…”
Section: Discussionmentioning
confidence: 93%
“…Though drug obtained from plant have limited chances of side but sometime improper dose can cause adverse effect of humans. Therefore toxicological study of various phytochemicals is must, Mariam et al (2013) studied the toxicological effect of B. aegyptiaca, and Jaundice, anthelmintic, rheumatism, CNS depressant, fungicidal, larvicidal, molluscicidal, insecticidal properties, it also used to remove intestinal parasites Neuwinger, 1996;Mohamed et al, 1999, Koko et al, 2000Koko et al, 2005;Chapagain et al, 2009;Patil et al, 2010;Abdulmalik et al, 2011;Shalaby et al, 2012 Stem/Root Bark Yellow fever, jaundice, antiangiogenic, antitumor, antioxidant, antimalarial, anti trypanocidal activity, cytotoxicity, mental diseases, diarrhea, epilepsy, treatment of Syphilis round worm infection, haemorrhoid, fish poison, antivinom against viper venom and syphilis Bukar et al, 2004;Katewa et al, 2004;Wurochekke & Nok, 2004;Koch et al, 2005;Gad et al, 2006;Ojo et al, 2006;Wufem et al, 2007;Ahmad Hassan et al, 2016 Fruit Skin diseases, sleeping sickness, oral hypoglycemia, cytotoxicity, antitumor effects, antioxidant, antifertility, insecticidal activity, anticonvulsant effect, cure mouth ulcer, boils and burns, whooping cough, effective antischistosomal remedy, act as an antidote to arrow poison Rao et al, 1997;Wiesman & Chapagain, 2003;Katewa et al, 2004;Koch et al, 2005;Koko et al, 2005;Gad et al, 2006;Ojo et al, 2006;Gnoula et al, 2008;Thirupathi et al, 2009;Al-Ghannam et al, 2013;Molla et al, 2013;Wabale, 2017 Seed Antitumor, anti-cancer antibacterial, antioxidant, antimalarial activity, effective antischistosomal remedy and cure cough, colic pain Wiesman & Chapagain, 2003;Bukar et al, 2004;Koko e...…”
Section: Toxicology Of Phytochemicalsmentioning
confidence: 99%
“…The bark, fruit and oil of tree have been widely used to treat various disease or disorders such as cancer (Gnoula et al, 2008;Hassan et al, 2016;Montasser et al, 2017), tuberculosis (Hassan et al, 2016), HIV/AIDS (Sheded et al, 2006;Alashaal et al, 2010), malaria (Kusch et al, 2011;Bobbo et al, 2016;Sibhat & Hiben, 2016), diabetes (Helal et al, 2013;Abou Khalil et al, 2016), sleeping sickness (Barley, 1962;Sheded et al, 2006;Alashaal et al, 2010), wounds (Chevallier et al, 2003;Kommu et al, 2013), colds, syphilis, liver and spleen disorders (Abdel-Kader et al, 2008;Zaahkouk et al, 2015), jaundice (Sarker et al, 2000;Abdulmalik et al, 2011), yellow fever, snake bite (Ojo et al, 2006) and aches (Mohamed et al, 1999;Hamid et al, 2001). The infusion of root bark has been used in diarrhoea, haemorrhoid and also acts as a fish poison (Bukar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Even in Japan and the United States of America, parity was associated with tooth loss as a result of caries or periodontal disease [12,13]. It is worthy of note that several studies conducted on pregnant mothers, who eventually become nursing mothers, revealed a poor oral health status [14][15][16]. There is a dearth of information on dental caries and risk indicators of caries among nursing mothers in Enugu, southeastern Nigeria.…”
Section: Introductionmentioning
confidence: 99%